Characterization of mixed lymphocyte reaction blocking antibodies (MLR-Bf) in human pregnancy - Agrawal Suraksha; Saxena Vijay; Pandey Manoj (BMC, 2003)
Abstract Background It is known that during normal pregnancy and after immunotherapy blocking antibodies are developed, these antibodies inhibit mixed lymphocyte reaction and are also anti-mitogenic in nature. Mixed lymphocyte reaction blocking antibodies are specific to the husband's lymphocytes. In the present study an attempt has been made to characterize the mixed lymphocyte reaction blocking antibodies in normal pregnancy and in women with recurrent spontaneous abortion after immunotherapy. Methods Serum was obtained from women of different gestational windows of pregnancy (Ist, IInd, IIIrd trimesters and post delivery period of normal pregnancy), recurrent spontaneous aborters from pre and post immunization. Healthy (male and females) controls were screened for the presence of mixed lymphocyte reaction blocking antibodies. The standard mixed lymphocyte reaction technique was used to evaluate the inhibitory effect of serum in the mixed lymphocyte reaction. Each serum was tested for cytotoxic antibodies. Immunoglobulin G and its isotypes were isolated according to the standard protocol. Results In the present study we have observed that there was significant inhibition of proliferation response when immunoglobulin G from different trimesters of pregnancy were added to one way mixed lymphocyte reaction or to phytohemagglutinin activated lymphocyte proliferation assay. Similar pattern was seen when immunoglobulin G isolated from adequately immunized women with recurrent spontaneous abortion was used. It was further confirmed that amongst all the isotypes of immunoglobulin G, only immunoglobulin G-3 was found to be positive for the inhibitory effect. Conclusions Present study indicates that mixed lymphocyte reaction blocking antibodies are immunoglobulin G-3 in nature. It is developed during pregnancy and also after immunotherapy in women with recurrent spontaneous abortion who subsequently have the successful pregnancy.